Effect of pruning intensity and foliar feeding of nutrients on growth, yield and quality of phalsa (Grewia subinaeqalis D.C.) (Indian Journal of Arid Horticulture, 2020)
Phalsa also known as star apple is subtropical fruit cultivated commercially in Punjab, Haryana, Uttar Pradesh, and Madhya Pradesh. It is also cultivated in limited scale in the states of Maharashtra, Gujarat, Andhra Pradesh, Bihar and West Bengal. Fruits are eaten fresh and juice is used for making squash and syrup, on other hand wood is used for fuel to rural people and used for basket making which income generating entrepreneurship to the rural formers and poor people. It is quick growing, hardy shrub thrive well in wide range of soils even on salt affected wastelands. Phalsa can also be grown as intercrop in mango, aonla, bael and ber orchards. Little information is available on pruning combined with foliar feeding of phalsa for better plant health and higher production of quality fruits which has good medicinal properties known since Vedic times.
Keywords: subtropical; Haryana